REBRANDING P.O EKA-MIRA SEBAGAI UPAYA MEMPERTAHANKAN BRAND LOYALTY - Arianto, Mukhammad Kiki; Budiardjo, Hardman; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Public transportation or public transport is a means of transportation when the passengers not traveling use his own vehicle. Public transportation deliberately provided for residents to fulfill transportation they do daily needs. With using a public transportation, many benefits that can be obtained the community. Business competition that is more strict now this caused many companies involved in the fulfillment of the needs and consumer advocacy. It is means that each companies should put orientation in customer satisfaction as the main objective of. Po Eka-Mira is the company that moves in transportation service, especially transport service passengers that provides armada-armada good in economy class and executive class. To the specifications bus, the economy class bus named Mira and an executive class bus named Eka. The research was done by using the method the qualitative study is by applying interview, Observation , documentation , and the literature study to get the data used as a support making the concept of design rebranding. The result of design rebranding this is to anticipate consumers who move ( brand loyalty ) to a product competitors because products competitors who has experienced reform in the design and services . Design for that rebranding it is certainly are also to be used to getting a new consumer. Keywords: Design, Rebranding, Bus, EKA-MIRA, Brand loyalty